AUSTRODIPLOSTOMUM COMPACTUM (LUTZ, 1928) (DIGENEA, DIPLOSTOMIDAE) INFECTING GEOPHAGUS PROXIMUS CASTELNAU, 1855 (CICHLIDAE, PERCIFORMES) IN THE TIETÊ RIVER, NOVA AVANHANDAVA RESERVOIR, MUNICIPALITY OF BURITAMA, SÃO PAULO STATE, BRAZIL - de Oliveira Penha Zica, Érica (2010)
This study aimed to evaluate the infection by the Austrodiplostomum compactum (Lutz, 1928) metacercariae in the eyes of Geophagus proximus Castelnau, 1855 from the NovaAvanhandava Reservoir, medium Tietê river, municipality of Buritama, São Paulo State,Brazil. The parasites were collected from vitreous humor, fixed in AFA solution under coverslip pressure, stained with carmine and cleared with creosote. The morphometric analysis was performed using a computerized system for analysis of images QWin Lite 2.5 (Leica). Fourtyone G. proximus specimens were collected and 38 were infected in the humor vitreous with A. compactum metacercariae (prevalence = 97%). Four hundred eighty six metacercariae were recovered, range from 1 to 194 in the studied specimens. The mean intensity of infection and abundance were 12.8 ± 5.1 and 11.8 ± 4.75, respectively.